Intestinal tract endometriosis - Galbfach, Przemysław; Dziki, Adam (Menopause Review/Przegląd Menopauzalny, 2007)
Endometriosis is defined as the presence of ectopic endometrium outside the uterine cavity. Endometriosis of the intestinal tract occurs at the rate of 3-37% of patients with pelvic endometriosis. Within the digestive tract, foci of endometriosis are usually found in the rectum and sigmoid colon. Intestinal foci of endometriosis are usually located on the external side of the bowel, encompassing serous membrane, muscular membrane and submucous lamina. Mucous membrane is rarely involved, thus creating considerable diagnostic problems. Symptoms are usually associated with menstrual cycle, exacerbating just before and during menstrual bleeding. The most frequent signs are: abdominal and pelvic pain, profuse menstrual bleeding, painful menstruation, dyspareunia, obstipation, ileus, diarrhoea, tenesmus and anal bleeding. In clinical practice endometriosis of the intestinal tract is rarely diagnosed and usually after long-lasting symptoms. Malignant transformation of bowel endometriosis is exceptional. Laparoscopy seems to be the best diagnostic method of intestinal endometriosis and its treatment is to remove the involved part of the bowel together with endometriotic foci and surrounding tissues. Cyclical intestinal endometriosis symptoms correlating with menstrual cycle should always draw our attention to this rare disorder.